Analisis Manajemen Pengumpulan dan Pendistribusian Zakat di BAZNAS Kabupaten Bima - Ditha Alfikroh; Rafiuddin; M. Rasyad Al Fajar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study was conducted to determine how the management of zakat collection and distribution is implemented at the National Zakat Agency (BAZNAS) in Bima Regency and to analyze the inhibiting and supporting factors of zakat collection and distribution at BAZNAS in Bima Regency. This study used a qualitative method with primary and secondary data sources. Primary data were obtained directly from the research object through interviews, while secondary data were used to support and strengthen the primary data. Thus, this study can obtain a more comprehensive and in-depth picture of the phenomenon under study. Secondary data sources were obtained from journals, books, reports, and other documents relevant to the research topic, to support and enrich the primary data obtained through interviews. The combination of primary and secondary data allows this study to provide a more complete and accurate picture of the phenomenon under study. The research results show that the National Zakat Agency (BAZNAS) of Bima Regency has developed a comprehensive zakat management system through a structured approach based on regulations, technology, and empowerment programs. The productive zakat model, with rigorous selection and ongoing mentoring, has successfully transformed mustahik into muzakki, reflecting Islamic distributive justice. However, challenges remain, ranging from low zakat literacy among the community, suboptimal coordination with the Zakat Management Unit (UPZ), to limited human resources and geographic limitations. On the distribution side, obstacles arise in the management of the still-nascent productive zakat system, the accuracy of fund allocation, and the misuse of aid. Nevertheless, BAZNAS has a strong foundation through its professional zakat collection system for civil servants (ASN), which generates Rp210 million per month thanks to the support of the Mayor's regulations. Innovations such as a digital database, a participatory approach, and simplified selection criteria demonstrate the commitment to system development. By combining existing strengths with creative solutions, BAZNAS of Bima Regency has the potential to become an effective zakat management model with a real impact on poverty alleviation.